Employment Effects of Economic Sanctions in Iran - Ali Moghaddasi Kelishomi; Roberto Nisticò (Institute of Labor Economics (IZA), 2021)
This paper investigates the effect of economic sanctions on employment. We exploit the imposition of a series of unexpected and unprecedented international economic sanctions on Iran in 2012 and estimate the short-run effects of the change in import exposure on manufacturing employment at the industry level. Our estimates indicate that the sanctions led to an overall decline in the manufacturing employment growth rate by 16.4 percentage points. However, we uncover significant asymmetric effects across industries with different ex-ante import shares. Interestingly, the effects are mostly driven by labor-intensive industries and industries that heavily depend on imported inputs. This suggests that the overall negative impact of the sanctions on employment might be largely due to the decline in productivity experienced by industries with a high propensity to import inputs from abroad.
Keywords: F16; F51; J21; 330; import exposure; employment; economic sanctions; labor reallocation